Endorsement of the Lisbon Outcome Statement and Launch of a National Programme for Age-Friendly Cities and Communities in Portugal - Miguel Arriaga PhD; Yon Yongjie PhD; Thiago Herick de Sa PhD; Ana Justo MSc; Gisele Câmara PhD; Andreia Costa PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Portugal is one of the European Union countries with the highest rates of people aged 65 or more. The old-age dependency index is the third highest in Europe. Longevity is a remarkable human achievement but without a comprehensive approach to fostering healthy ageing over the life-course, the burden on health and care systems and social services will increase. This issue is compounded as life expectancy rises, but many of these additional years are not lived in good health. Promoting healthy ageing is an essential political and moral strategy for the well-being both of individuals and societies. Concerning this, Portugal endorsed the Lisbon Outcome Statement drawn up based on the 2023 Regional Summit on Policy Innovation for Healthy Ageing and made its commitment for the creation of age-friendly environments. The National Programme for Age-Friendly Cities and Communities in Portugal is one of the first concrete steps to fulfill that endorsement.